2015
DOI: 10.3390/catal5020518
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Raman Monitoring during Photocatalytic Epoxidation of Cyclohexene over V-Ti/MCM-41 Catalysts

Abstract: A series of V-and/or Ti-loading MCM-41 catalysts are successfully synthesized with a hydrothermal method. The photocatalytic and thermal epoxidations of cyclohexene in the presence of tert-butyl hydroperoxide (t-BuOOH) were investigated with real-time monitored by NIR-Raman spectroscopy. It suggests that both V-and Ti-loading can be responsible for the cyclohexene epoxidation. Moreover, the complementary behavior of V-and Ti-loading may be related to a similar role of activation. Interestingly, the progress of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…When excess epoxide was present it was possible to isolate essentially pure cyclohexene oxide by simple decantation (see the Supporting Information). Unreacted acetophenone and the ester group were indicated by the carbonyl stretches 1683 and 1690 cm –1 of ketone and ester groups, respectively (Figure c,d). , It is evident from these data that aqueous DMAB can be used as a selective reducing agent for saturated aliphatic carbonyl compounds in the presence of conjugated carbonyl compounds, aryl alkyl ketones, and epoxides.…”
Section: Results and Discussionmentioning
confidence: 99%
“…When excess epoxide was present it was possible to isolate essentially pure cyclohexene oxide by simple decantation (see the Supporting Information). Unreacted acetophenone and the ester group were indicated by the carbonyl stretches 1683 and 1690 cm –1 of ketone and ester groups, respectively (Figure c,d). , It is evident from these data that aqueous DMAB can be used as a selective reducing agent for saturated aliphatic carbonyl compounds in the presence of conjugated carbonyl compounds, aryl alkyl ketones, and epoxides.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, M. A. Bañares et al [90] studied the photocatalytic epoxidation of cyclohexane in the presence of ter-butyl hydroperoxide (t-BuOOH) over VxTiy/MCM-41 catalyst under UV-light using the real-time NIR-Raman spectroscopy. In the experimental set-up (Fig.…”
Section: Operando Raman For Investigating Photocatalysis In Liquid-phasementioning
confidence: 99%
“…In accordance with the SciFinder data, for instance, operando Raman spectroscopy has triggered researchers high attention (by Oct. 2015, 187 papers included) because of the following factor: (1) it is sensitive to a tiny modification of the structure; (2) the Raman signal is less affected by the presence of H2O and other gases; (3) it could be operated in a broad temperature range 25~1000 ºC and pressure range 0.1~10.0 MPa. Using operando NIR-Raman, Banares and co-workers have studied the photocatalytic epoxidation of cyclohexene over V-based catalysts and revealed that the cyclohexene was directly photo-epoxidized to 1,2-epoxycyclohexane by t-BuOOH during the reaction [34]. Li's group has monitored the synthesis process of various catalytic materials, such as Fe-, V-, Mo-based and zeolite catalysts and so on, using operando UV-Raman [35].…”
Section: Monitoring Catalytic Reactions Using Operando Spectroscopymentioning
confidence: 99%